Structural performance of jointed reinforced concrete pavement slab with subbase erosion. (August 2020) - Elkholy, Said; El-Ariss, Bilal; Galal, Sameh
Abstract: Structural behavior of jointed reinforced concrete pavement (JRCP) slab is sensitive to the subbase erosion which is considered in pavement design as a potential failure mode. However, erosion of subbase has not been clearly addressed in the JRCP design specifications. The most widely used procedures for the design of pavement slabs is specified in the Guide for Design of Pavement Structures (AASHTO 1986, 1993, and 2008). In this study a simple but effective 2D finite element (FE) structural response model is proposed and utilized to examine the effect of subbase erosion on the JRCP slab performance. The FE model considers different JRCP slab thicknesses and dimensions and different subbase erosion scenarios. The results of the proposed FE model indicate that considering the subbase erosion in JRCP slab design may require a substantial increase in slab reinforcement; however, it can lead to less damage and longer lifespan of the pavement slab.